Electro-Reduction of Molecular Oxygen Mediated by a Cobalt(Ii)Octaethylporphyrin System onto Oxidized Glassy Carbon/Oxidized Graphene Substrate - Aguirre-Quintana, M; Aguirre-Quintana, M (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The oxygen reduction reaction (ORR) is the most important reaction in life processes and in energy transformation. The following work presents the design of a new electrode which is composed by deposited cobalt octaethylporphyrin onto glassy carbon and graphene, where both carbonaceous materials have been electrochemically oxidized prior to the porphyrin deposition. The novel generated system is stable and has an electrocatalytic effect towards the oxygen reduction reaction, as a result of the significant overpotential shift in comparison to the unmodified electrode and to the electrodes used as target. Kinetic studies corroborate that the system is capable of reducing molecular oxygen via four electrons, with a Tafel slope value of 60 mV per decade. The systems were morphologically characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM) Electrochemical impedance spectroscopy studies showed that the electrode previously oxidized and modified with cobalt porphyrin is the system that possesses lower resistance to charge transfer and higher capacitance. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.